Metody iteracyjne rozwiązania pewnego równania charakterystycznego - Wiśniewski, L. (Engineering Transactions, 1970)
In this paper are presented some methods solving the characteristic equation determining the critical loading of the solid wall rod webb at a complex state of stress. Two iteration methods of finding the coefficient y for calculating the value of the critical loading of the web are discussed: a) Osborne’s method of solving the problem det [P–γQ]= 0, b) an involution method in the equivalent problem det [PQ-1–yl] = 0, or det[P-1Q- λl] = 0.